Yoga for Chemotherapy-Induced Peripheral Neuropathy and Fall Risk: A Randomized Controlled Trial. Issue 6 (4th June 2020) - Bao, Ting; Zhi, Iris; Baser, Raymond; Hooper, Madeline; Chen, Connie; Piulson, Lauren; Li, Qing S; Galantino, Mary Lou; Blinder, Victoria; Robson, Mark; Seidman, Andrew; Panageas, Katherine S; et al.
Abstract: Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common, debilitating side effect that worsens quality of life and increases the risk of falls in cancer survivors. Evidence of yoga's safety and efficacy in treating CIPN is lacking. Methods: In a randomized controlled study, we assigned breast and gynecological cancer survivors with persistent moderate-to-severe CIPN pain, numbness, or tingling with a score of 4 or greater (0-10 numeric rating scale [NRS]) for at least 3 months after chemotherapy to 8 weeks of usual care or yoga focused on breathwork and musculoskeletal conditioning. Primary endpoint was treatment arm differences for NRS, and secondary endpoints were Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity subscale (FACT/GOG-Ntx), and Functional Reach Test after week 8. We tested treatment arm differences for each outcome measure using linear mixed models with treatment-by-time interactions. All statistical tests were two-sided. Results: We randomly assigned 41 participants into yoga (n = 21) or usual care (n = 20). At week 8, mean NRS pain decreased by 1.95 points (95% confidence interval [CI] = -3.20 to -0.70) in yoga vs 0.65 (95% CI = -1.81 to 0.51) in usual care ( P = .14). FACT/GOG-Ntx improved by 4.25 (95% CI = 2.29 to 6.20) in yoga vs 1.36 (95% CI = -0.47 to 3.19) in usual care ( P = .035). Functional reach, an objective functional measure predicting the risk of falls, improved by 7.14 cm (95% CI = 3.68 to 10.59) in yoga and decreased by 1.65 cm (95% CI = -5.00 to 1.72) in usual care ( P = .001). Four grade 1 adverse events were observed in the yoga arm. Conclusion: Among breast and gynecological cancer survivors with moderate-to-severe CIPN, yoga was safe and showed promising efficacy in improving CIPN symptoms.